THE EFFFECTIVENESS OF KAHOOT APPLICATION TOWARDS STUDENTS’ GOOD FEEDBACK PRACTICE - Omar, Nurul (PEOPLE: International Journal of Social Sciences, 2017)
Many educators started to utilize technology application activities in the classroom as an attempt to attract students’ attention and motivate their classroom participation. Kahoot is an example of a technology assessment tool that includes students’ participation in answering MCQ-type of questions in a more competitive environment. However, there are concerns about the ability of Kahoot application in gauging students’ feedback practice. As Kahoot is known to be an interactive approach in conducting quizzes or tests, it is a wonder if it can also be a good platform for giving feedback. In this study, the author will discuss the effectiveness of Kahoot application as an assessment tool in classroom activities following the guideline of seven principles of good feedback practice. A qualitative approach utilizing data from three focus group discussions was done in a group interview setting with a case study on 15 students undergoing Diploma in Communication and Media Programme. The findings present students’ perspective on the effectiveness of Kahoot assessment towards their good feedback practice. By assessing the application, it contributes towards understanding the strength and weaknesses on the usage of technology assessment in classroom activities